Islamic Psychological Approach in Forming Student Character Through Islamic Religious Education Learning at Nurul Qodiri Integrated Vocational School - Cindy Oktvita Jely; Irhamudin; Adi Wijaya (Journal of Research in Islamic Education, 2026)
This study aims to analyze the application of an Islamic psychology approach in Islamic Religious Education (PAI) learning and its role in shaping student character at Nurul Qodiri Integrated Vocational School. This study used a qualitative approach with field research. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results showed that the application of Islamic psychology was carried out through role models, habituation, advice, and a personal approach to students. This approach was able to shape student character, especially in aspects of discipline, responsibility, honesty, and religiosity. Thus, Islamic psychology-based PAI learning has proven effective in integrating cognitive, affective, and spiritual aspects, and contributes to the development of students' character as a whole.